2019
DOI: 10.1021/acsinfecdis.9b00199
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Escherichia coli and Shigella spp. by Nuclear Magnetic Resonance Based Metabolomic Characterization of Culture Media

Abstract: Dysentery is a major health threat that dramatically impacts childhood morbidity and mortality in developing countries. Various pathogenic agents cause dysentery such as Shigella spp. and Escherichia coli, which are very closely related if not identical species. Sensitive and precise detection and identification of the infectious agent is important to target the best therapeutic strategy but the differential diagnosis of these two groups remains a challenge using conventional methods. Here we present a nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Globally, NTS is estimated to result in 90 million illnesses and 155,000 deaths per year [64]. In the United states, 40,000 infections and 450 deaths are reported annually as a result of NTS infection [45,64]. Children and immunocompromised youths have a higher risk of infection, with the latter being more susceptible for more severe disease manifestations or death [64].…”
Section: Salmonellamentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, NTS is estimated to result in 90 million illnesses and 155,000 deaths per year [64]. In the United states, 40,000 infections and 450 deaths are reported annually as a result of NTS infection [45,64]. Children and immunocompromised youths have a higher risk of infection, with the latter being more susceptible for more severe disease manifestations or death [64].…”
Section: Salmonellamentioning
confidence: 99%
“…Treatment of Salmonella infection often includes lessening of symptoms and administration of antibiotics [65]. To provide accurate diagnosis of salmonellosis, the current practice is to collect stool samples from patients and culture them in Salmonella selective media [45,64,65]. In this method, enrichment broths suited for enhanced isolation of Salmonella may be used to increase diagnostic accuracy [65,66].…”
Section: Salmonellamentioning
confidence: 99%
“…coli ( Pupo et al, 2000 ), while pH-indicator-based triple sugar ion (TSI) test showed poor sensitivity and specificity in terms of discriminating E . coli and Shigella spp., from other bacterial species ( Rautureau et al, 2019 ). Other methods commonly used in clinical laboratory such as 16S rRNA gene sequencing and matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS) cannot differentiate Shigella spp., from E .…”
Section: Introductionmentioning
confidence: 99%
“…From clinical perspective, Shigella spp., are responsible for life-threatening dysentery (also known as shigellosis) and the infection leads to high childhood morbidity and mortality globally ( Wang et al, 2019 ; Zhu et al, 2020 ), while E . coli are normally commensals found in human gut microbiota ( Rautureau et al, 2019 ). However, among the many E .…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics, the comprehensive measurement of metabolites in a system, is a promising technique in this case because of its speed in delivering results [3]. Nuclear magnetic resonance (NMR) metabolomics has been proposed as a method to distinguish between E. coli and Shigella strains [4].…”
Section: Introductionmentioning
confidence: 99%